Circuit modeling for electromagnetic compatibility - Darney, Ian B. (Edison, NJ SciTech Publishing, 2013)
The book reviews developments in the following fields: electromagnetic compatibility; lumped parameter models; transmission line models; antenna models; transient analysis; bench testing; and system design.
Electronic reproduction.
Keywords: Electromagnetic compatibility; Electric circuits; Antennas (Electronics).; Electric lines; Electric power transmission; Lumped elements (Electronics).; Transients (Electricity).; Electronic books